Safety Evaluation of Diagnostic Laboratories of Hospitals Affiliated to Iran University of Medical Sciences in 2019 - Ebrahim Hassanzadeh; Edris Hassanpoor; Seyed Sajjad Razavi; Mohammad Reza Sheikhy-Chaman (Tehran University of Medical Sciences, 2020)
Background and Aim: Human resources are one of the most important assets of any organization and the creation of a safe working environment enhances the quality of services in addition to satisfying this valuable capital. The purpose of this study was to evaluate the safety of diagnostic laboratories of hospitals affiliated to Iran University of Medical Sciences(IUMS). Materials and Methods: This cross-sectional descriptive study was conducted in 7 IUMS hospitals in 2019. Data collection was performed using a checklist that was validated after being translated(by qualitative face validity method); Then, the safety status of the studied laboratories was classified into four categories: Excellent, good, average and poor. Finally, data were analyzed using descriptive statistics and SPSS software. Results: In determining the validity of the checklist using qualitative face validity, expertschr('39') opinions were applied as changes in the tool. In the descriptive part of the study and among the safety dimensions of diagnostic laboratories, the highest mean score was related to the dimensions of "communication hazards" and "safety information" and the lowest to the dimension of "fire safety". Conclusion: According to the results of the study, the overall safety status of the diagnostic laboratories of the hospitals under investigation is at a good level; however, the "fire safety" component as one the most important safety components was considered poor, and necessary steps must be taken to improve it.